Small-scale farmers' stewardship in the anthropocene : a natural experiment on the adoption of "New Theory Farming" practices for sustainable livelihoods in Ayutthaya Province, Thailand - Adeel, Sultan; Yaseen, Muhammad; Datta, Avishek; Khan, Syed Shurid; OAAA Residual; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Agriculture, characterized by small-scale farmers, provides food and fiber to the economy; however, it faces climatic changes, resource depletion, and biodiversity loss in the ongoing epoch, the Anthropocene. This calls for farmers{u2019} stewardship in terms of their land management practices for sustainable livelihoods. In this context, Thailand follows 2New Theory Farming3 (NTF) practices, requiring farmers to arrange their agricultural land into a ratio of 30:30:30:10 for pond, rice, orchard, and dwelling. Although the literature lauds their theoretical application for sustainable livelihoods, the practical implication of NTF practices still lacks grassroots-level evidence. To this end, this study utilizes the natural experimental design to examine the adoption of NTF practices through proportionally selected 210 small-scale farmers from six districts of Ayutthaya. Using the lens of Diffusion of Innovation Theory and the framework of Vijitwrannont et al. (2023), this study conceptualizes socioeconomic, demographic, crop-specific, psychological, and institutional factors as explanatory variables impacting the adoption of NTF practices, analyzed through binary logit model and propensity score matching (PSM) technique to calculate the likelihood of adoption. The results of an adoption index suggest moderate-level (49%) compliance with NTF practices. Adopters differ significantly from non-adopters on crop yield, crop income, self-efficacy, motivation, perceived benefits, social norms, risk acceptability, and access to information. The significant factors increasing the adoption likelihood are farmers{u2019} access to information via print media, community leaders, and the Late King Rama (IX), higher yields, crop income, age (higher), self-efficacy, motivation, perceived benefits, and social norms, while the factors limiting the adoption are farmers{u2019} access to information via government officials, marketers, and/or friends, gender (women), personal business as a primary income source, and risk aversion. The propensity score model suggests that NTF adopters gain 39 kilograms of higher crop yield per rai and an additional 191.8 Thai Baht (USD 5.86) per ton in crop income. These results add to the literature on NTF practices by developing an adoption index and applying PSM to indicate a precise increase in crop yield and income. The implications are important for community leaders, officials, and policymakers to support sustainable development goals and ensure sustainable livelihoods.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2025
Keywords: Economics -- Philosophy; Sustainable agriculture -- Thailand -- Ayutthaya; Farms, Small, -- Thailand -- Ayutthaya